EFL Teacher's Perceptions about Communicative Strategies in Uzbekistan - Muqimxo‘jayeva Xushnoza Ulug‘bekxo‘ja qizi, Kosimova Mukammal Umaraliyevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This study examines EFL teachers' perceptions of communicative strategies in Uzbekistan, revealing generally positive attitudes towards these methods for enhancing student engagement and language proficiency. However, significant challenges such as resource constraints and insufficient training impede their effective implementation. Despite these obstacles, innovative and resourceful teachers have found success in integrating communicative approaches into their classrooms.